O dumping social no direito do trabalho brasileiro - Amorim, Kelly Karynne Costa (2018)
This dissertation analyses the figure of social dumping in Brazilian law, analysing primarily the Constitution of the Republic of 1988 with regard to the tutelage of the worker and of the work enjoying the role of the employment relationship and the labour law As a beacon of the foundations of the Republic of free enterprise and the appreciation of work. It is also essential to analyze the assumptions of the employment relationship and its standardization, in addition to the generalization (or not) of labor law in the Brazilian economy and society, as well as the relevant challenges. However, the fact that the Federal Constitution ensures social rights and the infra norms of its application, standardization does not guarantee the effectiveness, with a view to the fierce competition in a competitive and globalized world. Based on this assumption, the failure to comply with the law of labor and the Federal Constitution is a reality and impacts on the life of the worker, but not only this, but the society in general. The term dumping came from international trade law to set up the leslealdade of competition between exporting countries selling their products below the normal value considered by the market in order to decrease or even aniquiar competition . Of the term dumping derives the term social dumping, considered, thus, as the reiterated and conscious practice of cheapening of products or only greater economic benefit to the detriment of disrespect to labor social rights that impact related areas, Social security, tax law and the working environment. In this scenario, it seeks to bring reflections on the Brazilian legal system and of the challenges that permeate the institute, the example of its constituent elements, granting of compensation for its practice, legitimacy of filing of the action for the election of Compensation and other potential of the theme.